Perbedaan Efektifitas Kompres Air Hangat dan Daun Kembang Sepatu Dalam Menurunkan Suhu Tubuh Balita Saat Demam - Sari, Rahmadah; Salmarini, Desilestia Dwi; Zulfadhilah , Muhammad (Pusat Riset dan Inovasi Nasional, 2024)
The impact of LBW poses many risks regarding problems in the body's system due to unstable body condition which can cause death. The causes of LBW are due to fetal factors, placental factors and maternal factors. Preeclampsia is a problem of serious maternal factors and has a high level of complexity. The results of the preliminary study in 2021 totaled 34 people with preeclampsia and 60 cases of low birth weight babies. Research objective is to determine the effectiveness of compresses of warm water and hibiscus leaves in lowering the body temperature of toddlers in the Banua Lawas Health Center area. The research methods is Quasi-experimental research with a pre-test-post-test research design without a control group. A sample of 30 people were divided into warm water compress groups and hibiscus leaf compress groups. Collecting data by observing according to SOP (Standard Operating Procedure). Data analysis using wilxocon. Resulted that the mean temperature in the warm water compress group before being given was 36.9°C and after being given was 36.3°C (the difference was 0.58°C). The average temperature in the hibiscus leaf compress group before being given was 36.8 °C and after being given 36.1 °C (the difference was 0,33 °C). There is a difference between warm water compresses and hibiscus leaves in reducing temperature in toddlers with fever in the Banua Lawas Health Center area (p-value ˂ 0.000). Concluded that both types of compresses are effective in reducing body temperature in children with fever but warm water compresses are more effective than hibiscus leaf compresses.